Performance Analysis of Non Burn Cooking Device Using Commercial Grade Quicklime as Heating Fuel - Dhakal, Niswan; Ale, Bhakta Bahadur; Bhattarai, Nawraj (Kathford Journal of Engineering and Management, 2018)
The need for portability and easy to handle devices has been felt by the trekkers and campers. In a country like Nepal, with tough geographical terrain and changing climates, a non burn cooking alternative is sought for outdoor cooking. Quicklime or Calcium Oxide (CaO) is commercially available in abundance. CaO releases 64 kJ of heat during slaking at Normal temperature and Pressure. Boiling of water, preparing tea, boiling egg, preparing omelet and preparing instant noodles were tested with an average of 32.7 % deviation from theoretical values without considering the manufacturing specification of 90 % purity. Calculating with the manufacturing specification, the error reduced to 27.3 %. Though cooking is correlated to the subjective preference of individuals, the highest cooking temperature was recorded 86.5 °C (boiling water), and the highest temperature of inner pot reached was 121.1 °C in that case. The highest temperature reached in each of cooking purposes were respectively as; boiling egg on water(75.6 °C), boiling egg without using water (11.2 °C), preparing tea(85.9 °C) and preparing instant noodles (68.3 °C). The quantity of cooing material resulted in higher efficiencies as evident by the factor that minimum deviation from theoretical calculation was seen during the cooking of noodles (17.5 %) and the maximum deviation was observed during preparation of boiled egg without using water or secondary pot (58.5 %). The device was not found financially feasible for household cooking and for cases where transportation cost incurred is high; the device was financially feasible (Rs. 14 as compared to above Rs. 400 and Rs. 250 of LPG based and kerosene based cooking respectively).